Peran Supervisi Pendidikan dalam Meningkatkan Mutu Pendidikan - Dina Ratna Sari; Asmendri Asmendri (Departement of Mathematics Education, 2022)
Education in Indonesia is still low even though Indonesia is a country that has a lot of Human Resources (HR). however, these human resources are unable to compete internationally, one of which is due to low achievement. This research is a literature study on the quality of education in Indonesia. This study aims to analyze the role of educational supervision in improving the quality of education. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Data sources are obtained through library study techniques that refer to sources available both online and offline such as: scientific journals, books and news sourced from reliable sources. The results of the study concluded that Supervision is designed to develop and improve the professionalism of teachers so that the teacher can develop in his work. The goal is to improve the effectiveness and efficiency of the teaching and learning process. Supervision is an assistance to teachers in improving teaching and learning situations. The results of the study show that educational supervision has a function in the form of a coordinator, consultant, evaluator. The steps in supervising are divided into 3 steps, namely: planning, implementing, evaluating.